Resistance training in face of the Coronavirus outbreak: Time to think outside the box - Gentil, P.; Ramirez-Campillo, R.; Souza, D. (Frontiers in Physiology, 2020)
The Problem: Resistance training (RT) is an exercise type commonly associated with the performance of muscle contractions against external resistance. This training model is very popular and has been recommended as an essential part of an exercise program by several important associations (ACSM, 2009; Garber et al., 2011). Its benefits are commonly associated with muscle strength and mass gains and expand to several areas such as blood pressure control (MacDonald et al., 2016), improved bone mineral density (Zhao et al., 2015), depression management (Gordon et al., 2018), cancer treatment (Fuller et al., 2018), controlling blood glucose (Codella et al., 2018), weight management (Paoli et al., 2014), among others. Such benefits, largely mediated by strength gains, culminate in reductions in mortality rates in different populations (Ruiz et al., 2008; Artero et al., 2011; Ortega et al., 2012; Hardee et al., 2014; Dankel et al., 2016). Many of the problems that RT has been shown to counteract are related to increased mortality and morbidity associated with COVID, like hypertension, diabetes, coronary diseases, overweight (Muniyappa and Gubbi, 2020; Salerno et al., 2020; Shahid et al., 2020; Singh et al., 2020; Zhou et al., 2020). Although it is not possible to attribute a direct cause-effect relationship between RT and mortality risk during COVID, it might be important to perform RT to improve general health and help in a better prognostic in case of contamination.